2020
DOI: 10.1101/2020.04.02.20051029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic Management of COVID-19 Patients: A systematic review

Abstract: Background: SARS-CoV-2 is the cause of the COVID-19 that has been declared a global pandemic by the WHO in 2020. The COVID-19 treatment guidelines vary in each country, and yet there is no approved therapeutic for COVID-19. were included. The search terms included combinations of: COVID, SARS-COV-2, glucocorticoids, convalescent plasma, antiviral, antibacterial. There were no restrictions on the type of study design eligible for inclusion. Results:As of March 26, 2020, of the initial manuscripts identified (n=… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(139 citation statements)
references
References 57 publications
0
133
1
5
Order By: Relevance
“…Remdesivir should also not associate to rifampicin in COVID-19/TB co-infection because of strong induction [64]. A recent review has reported that chloroquine phosphate and hydroxychloroquine showed favorable outcomes in the recovery of COVID-19 patients [65][66][67][68][69]. Both chloroquine and hydroxychloroquine are metabolized by hepatic cytochrome P450 enzyme 2D6 (CYP2D6) [70].…”
Section: Tb Diagnosis In Covid-19/hiv Co-infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Remdesivir should also not associate to rifampicin in COVID-19/TB co-infection because of strong induction [64]. A recent review has reported that chloroquine phosphate and hydroxychloroquine showed favorable outcomes in the recovery of COVID-19 patients [65][66][67][68][69]. Both chloroquine and hydroxychloroquine are metabolized by hepatic cytochrome P450 enzyme 2D6 (CYP2D6) [70].…”
Section: Tb Diagnosis In Covid-19/hiv Co-infectionmentioning
confidence: 99%
“…A study showed an association between corticosteroid use and lower mortality in COVID-19 patients [69]. Using a glucocorticoid in the early stages of the prognosis for a brief period of time could minimize the in ammation, but longer-term use could result in the risk of HIV and/or TB activation and even lack of treatment with TB.…”
Section: Tb Diagnosis In Covid-19/hiv Co-infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ever since the outbreak, the healthcare team and researchers across the globe have proposed several pharmacological interventions that could prove effective in treating COVID-19 (22). Various treatment options include, but are not limited to, antivirals and combinations, angiotensin receptor blockers, antimalarial, antihistamines, steroids, antipyretics (23).…”
Section: Pharmacological Management Of Pregnant Women With Covid-19mentioning
confidence: 99%